THE AC-FIELD SPECTROSCOPIC CHARACTERISTICS OF DOUBLE QUANTUM DOTS - Gihan H. Zaki; Ayman S. Atallah; Adel H. Phillips
The quantum transport characteristics for double quantum dots coupled weakly to conducting leads are studied under the influence of an AC-field of a wide range of frequencies. A numerical calculation shows the following features: (i) Two resonant peaks appear for the dependence of the normalized conductance G on the bias voltage, V0. The peak heights decrease as the frequency of the imposed AC- Field increases in the case of absorption of photons. However, in case of emission of photons the peak heights increase with the frequency. (ii) The calculated value of the activation energy of the electron required for quantum transport shows a dependence on the frequency of the absorbed (or emitted) photons.
Keywords: Physics; Optics